Pendampingan Pengukuran Tumbuh Kembang Untuk Pemantauan Status Gizi dan Perkembangan Balita - Agustina; Maritalia, Dewi; Mauyah, Nizan (LOSARI DIGITAL, 2024)
Abstract The implementation of Early Detection Stimulation, Growth and Development Intervention in Children is currently being strengthened through the Republic of Indonesia Minister of Health Regulation Number 25 of 2014 concerning Child Health Efforts and the Republic of Indonesia Minister of Health Regulation Number 66 of 2014 which states that Monitoring Children's Growth and Development through Early Intervention Detection Stimulation of Growth and Development is part of health services. carried out on babies, toddlers and pre-school children aimed at improving the continuity and quality of life of children. The method used in this activity of assisting in measuring growth and development for monitoring the nutritional status and development of toddlers is the individual approach method. This method emphasizes the process of empowering human resources to improve services, namely monitoring the growth and development of toddlers. Individual empowerment is expected to build awareness of critical thinking, positive and independent behavioral changes based on universal human values. The community service partner is PAUD Dian Persada which is located in Samuti Krueng Village, Gandapura District, Bireuen Regency, Aceh Province. Anthropometric measurement assistance was provided to Dian Persada PAUD Teachers, totaling 6 people, for approximately 2 (two) months, namely from July to August 2023. There was an increase in participants' knowledge regarding the measurement and growth of toddlers, which was marked by an increase in the average pre and post test was 4.17. There was an increase in participants' skills in measuring children's weight (BB), height (TB) and head circumference (LK). There was an increase in participants' skills in determining the nutritional status and development of toddlers based on the Pre-Developmental Screening Questionnaire (KPSP).